Józef Górski, At the Turn of History - Jan Grabowski (Zagłada Żydów)
Presented below is a fragment of Józef Górski’s diaries regarding the situation in Podlasie in the first years of the German occupation. It illustrates the author’s view on “the final solution of the Jewish question”. Górski himself says that he looked at the Holocaust as a Christian, who feels compassion for the victims, and at the same time as a Pole and a faithful follower of Roman Dmowski. From the latter point of view, he clearly welcomed the Holocaust. Józef Górski’s diaries could certainly be classified as an “oddity”, and as one reads them a number of painful questions arise, primarily about the scale of (silent) consent to the murder. In other words, to what extent did Górski’s clear (although frightening) views fit the framework of the “ordinary people” of occupied Podlasie?